The role of universities in knowledge production - Sutz, Judith (Himalayan Journal of Sciences, 2007)
To increase their contribution to development through the production and distribution of knowledge, universities in developing countries need to transform themselves into ‘developmental universities’. But to achieve this, other participants, such as industry and government, must be also be prepared to take on new responsibilities. No ready-made model exists to guide these changes; they will require both creativity and the willingness to engage in thoughtful dialogue, both within and outside universities.Himalayan Journal of Sciences 3(5) 2005 p. 53-56